IR and X-ray photoelectron spectroscopy of V2O5, TiO2 and V/Ti-oxide sol-gel derived films - Mandrino, Đorđe (Kovine zlitine tehnologije, 1998)
V/Ti-oxide films were prepared by deep-coating from sols made by mixing of V-oxisopropoxide and Ti-propoxide in V:Ti molar ratio in precursors 3:1, 1;1 and 1:3. Amorphous films were obtained after annealing at 300°C (1 h)). IR spectroscopic analysis revealed that V=Ostretching modes appeared at 1020 ?$cm^{-1}$? in the IR spectrum of powder (V:Ti = 1:1). however in the IR spectra of a film with the same molar ratio the bands at 1008 and 914 ?$cm^{-1}$? appeared suggesting the presence of ?$V^{4+}$?-O bonds. The new band at 790 ?$cm^{-1}$? signalled the V-O-Ti bridging bonds connection V-O and Ti-O polyhedra. XPS measurements confirmed that initial-state films contained ?$V^{5+}$?, ?$V^{4+}$? and ?$Ti^{4+}$? species, but at the film sufrace only ?$V^{5+}$? species existed. Sequential depth analysis of films performed with ?$Ar^+$? sputtering showed that the vanadium is reduced to 3+ oxidation state with progressive exposure while titanium is not affected.
Keywords: kovinski oksidi; titan; tanki filmi; vanadij; infrardeča spektroskopija; rentgenska analiza; sol-gel postopki